BANKING CONCENTRATION AND BANKING PRICES: THE ROLE OF CRUDE OIL PRICES - Abubakar Faruku; Ei Yet Chu (International Journal of Accounting, Finance and Business, 2020)
The degree of competition in the Nigerian banking sector matters for the efficiencyof the production of banking services, the quality of banking products, and the degree ofinnovation in the banking sector. Given the heavy dependence of Nigerian economy on crudeoil prices and the need to develop robustness in the performance of banking institutions inNigeria, this study, which is based on the structure conduct performance (SCP) hypothesis,examines the effect of banking concentration on Nigeria banks’ pricing. The study alsoinvestigates the impact of crude oil prices on banking concentration and its effects on bankprice. This study adopts the panel static model that involves panel ordinary least squares, fixedeffect model, and random effect model to test the empirical model. This study sampled 13licensed commercial banks in Nigeria for the period 2014-2018. Findings reveal that bankconcentration positively affect bank prices. It also shows that crude oil has a negative impacton bank prices. By implication, the role of crude oil can reduce bank competition through bankprices. However, high bank concentration can reduce the crude oil effect on bank prices.